Implikasi Perubahan Derivasi dan Makna ”أخرج” dalam Juz ‘Amma - Mochamad Fawaidur Rochman; Nila Alimatun Nazilah; Nila Alimatun Nazilah (Al-Lahjah, 2022)
Arabic is a language that is rich in vocabulary vocabulary. Sometimes one word in Arabic will collect various kinds of meanings which vary out of the real meaning, changes in derivation can also change the meaning of meaning in the form of sentence structure that influences the change of meaning in the sentence by updating the existing context. This study uses qualitative methods with a content analysis model. Requesting akhrama and derivation of data collected through written documentation (Al Qur'an) and instructions for recording data. Then the data is analyzed qualitatively to examine the morphological meaning of the sentence and its grammatical variation in meaning. From this study found the word akraja and its derivatives contained in the Koran received oada juz 30 with 5 forms of sentences in 5 surah, among others: surah An-Naba 'in verse 15, An-Nazi'at verses 29 and 31 , Al-A'la in verse 8, Az-Zalzalah in verse 2. In the 5 surahs it is 3 sentences in the original derivation and 2 sentences that change the change from the derivation. 3 sentences containing fiil madhi and 2 sentences consisting of fih mudhore 'which stores dhomir huwa and dhomir bariz muthasil by estimating dhomir nahnu and changing their meanings according to the form of kalam (siakul kalam).